Ethnobotanical Uses and Pharmacological Activities of Moroccan Ephedra Species - Chroho, Mounia; Bailly, Christian; Bouissane, Latifa (Planta Medica, 2024)
Ephedra species are among the most popular herbs used in traditional medicine for a long time. The ancient Chinese medical book “Treatise on Febrile Diseases” refers to the classic traditional Chinese medicine prescription Ge Gen decoction, which consists of seven herbs, including an Ephedra species. Ephedra species are utilized all over the world to treat symptoms of the common cold and coughs, and to combat major human diseases, such as asthma, cancers, diabetes, cardiovascular and digestive disorders, and microbial infections. This study aimed at identifying specific Ephedra species used traditionally in Morocco for therapeutic purposes. The plant parts, their preparation process, and the treated pathologies were identified and analyzed. The results revealed five ethnobotanically important species of Ephedra: Ephedra alata Decne, Ephedra altissima Desf., Ephedra distachya L., Ephedra fragilis Desf., and Ephedra nebrodensis Tineo. These species are used traditionally in Morocco for treating people with diabetes, cancer, rheumatism, cold and asthma, hypertension, influenza virus infection, and respiratory ailments. In addition, they are occasionally used as calefacient agents, to regulate weight, or for capillary care. Few studies have underlined the antibacterial and antioxidant activities of some of these Moroccan Ephedra species, but little information is available regarding the natural products at the origin of the bioactivities. Further phytochemical investigations and clinical data are encouraged to better support the use of these plants.
Keywords: Ephedra; Ephedrae herba; plants from Morocco; traditional uses; biological activities